Halal Awareness dan Diskon dalam Keputusan Pembelian DRW Skincare - Sulalah; Wardatus Syarifah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to examine the influence of halal awareness and discounts on purchasing decisions for DRW Skincare products at the Masaran Sentol Laok Sumenep branch. This research is based on the increasing need for skincare products among Muslim consumers and the growing importance of halal assurance in consumer behavior. In addition, discount strategies are also considered capable of influencing purchasing decisions. This study used a quantitative approach with a survey method. The population consisted of consumers of DRW Skincare at the Masaran Sentol Laok Sumenep branch, with 55 respondents selected as the sample. Data were collected through questionnaires and analyzed using multiple linear regression, partial test, and simultaneous test. The results show that halal awareness has a positive effect on purchasing decisions. Discounts also have a positive effect on purchasing decisions. Simultaneously, halal awareness and discounts influence consumer purchasing decisions for DRW Skincare products. These findings indicate that halal assurance and promotional strategies are important factors in strengthening consumer trust and encouraging purchasing behavior.